A branch and bound and simulated annealing approach for job shop scheduling - Tan, Hui Woon; Salim, Sutinah (Department of Mathematics, Faculty of Science, 2004)
This paper presents two approaches to the solution of the job shop scheduling problem, namely the branch and bound, and simulated annealing approach. The objective is to schedule the jobs on the machines so that the total completion time is minimized. In the branch and bound approach, the job shop scheduling problem is represented by a disjunctive graph, then the optimal schedule is obtained using the branch and bound algorithm while simulated annealing is a local search based algorithm which will slightly perturb the initial feasible solution to decrease the makespan.